The Use of the General Animal-Based Measures Codified Terms in the Scientific Literature on Farm Animal Welfare - Brscic, Marta; Contiero, Barbara; Magrin, Luisa; Riuzzi, Giorgia; Gottardo, Flaviana (Frontiers in Veterinary Science, 2021)
The approach to farm animal welfare evaluation has changed and animal-based measures (ABM), defined as the responses of an animal or effects on an animal, were introduced to assess animal welfare. ABM can be taken directly on the animal or indirectly and include the use of animal records. They can result from a specific event or be the cumulative outcome of many days, weeks or months. The objectives of the current study were to analyze the use of general ABM codified terms in the scientific literature, the presence of their definitions, and the gap mapping of their use across animal species, categories, years of publication and geographical areas of the corresponding author institution. The ultimate aim was to propose a common standard terminology to improve communication among stakeholders. In this study, data models were populated by collecting information coming from scientific papers extracted through a transparent and reproducible protocol using Web of ScienceTM and filtering for the general ABM codified terms (or synonyms/equivalents). A total of 199 papers were retained and their full texts were assessed. The frequency of general codified ABM terms was analyzed according to the classification factors listed in the objectives. These papers were prevalently European (159 documents) and the mostly represented species was cattle. Fifty percent of papers did not provide a definition of the general ABM terms and 54% cited other sources as reference for their definition. Results of the study showed a very low penetration of the general codified ABM term in the literature on farm animal welfare, with only 1.5% of the papers including the term ABM. This does not mean that specific ABM are not studied, but rather that these specific ABM are not defined as such under a common umbrella, and there is no consensus on the use of terminology, not even among scientists. Thus, we can not expect stakeholders to use a common language and a standardized terminology. The recognition and the inclusion of ABM in the lists of the commonly accepted abbreviations of the scientific journals, could be a first step to harmonize the terminology in the scientific literature.